Boardroom Disputes : How to Manage the Good, Weather the Bad, and Prevent the Ugly - International Finance Corporation (International Finance Corporation, Washington, DC, 2017)
A dynamic board seeks to stimulate the flow of ideas, identify key issues, consider alternatives, and make informed decisions. And for that you need deliberation and debate. But these positive processes can sometimes turn into boardroom disagreements that must be dealt with properly and promptly; otherwise, they can devolve into acrimonious disputes that undermine the board’s effectiveness and the company’s performance. This paper describes key steps that boards can take to mitigate the impact of disputes, and, even better, to minimize the risk of disputes arising in the first place. It is intended as companion and post-training material for a course called ‘managing disputes and difficult conversations on the board.’ This highly interactive course for board directors was created by the IFC Corporate Governance Group in partnership with the Center for Effective Dispute Resolution (CEDR). It is designed to help directors understand board conflict and conflict styles, and it covers difficult scenarios that directors often encounter. The course offers guidance and practical tips for how to have a difficult conversation; for handling avoidance, high emotions, and status issues; and for breaking through deadlock, and how to apply these skills specifically in a board context. This publication also can be used as stand-alone guidance for boards. While the training itself focuses heavily on individual development of interpersonal skills relevant in the board context, this publication also deals with the board as a collective body that needs to cultivate its ability to manage disputes effectively, starting by establishing good corporate governance policies and practices.